ANALISIS FAKTOR-FAKTOR PENGARUH KONFLIK (DISPUTE) TERHADAP KEBERHASILAN PROYEK KONSTRUKSI DI PROVINSI ACEH - Rinaldy Rinaldy; Teuku Budi Aulia; Anita Rauzana (JURNAL TEKNIK SIPIL, 2017)
Abstract: In the implementation of projects often arise constraints, if the project objectives are not achieved properly. These problems if not managed properly then it will be a conflict (dispute) or disagreement between the elements involved in the implementation of the project. This study aims to identify the factors and the dominant factors that cause conflict in construction projects in the province of Aceh, as well as analyzing the forms of relationships and the influence of factors of conflict the success of construction projects in the province. Observed projects are construction projects that have been completed starting from the year 2008-2015, with funding coming from APBA and APBK.. Factors that cause conflicts in the implementation of construction projects in Aceh province was caused by the owner of factors, factors consultants, contractors factors, factors project conditions, the human factor, and the factor of the contract and specifications. The dominant factor causing conflicts in the implementation of construction projects in the province of Aceh is due to factors owner, with a mean value of 4.253. Relationship conflict factors to the success of construction projects in the province of Aceh, is to have a relationship with a very high correlation coefficient of 0.921. The influence factors of the conflict on the success of construction projects in the province of Aceh, the most influential factor is the condition of the project, with a regression coefficient of 1.021. This suggests that if the project conditions factor handled well, while other factors remain, then the success of construction projects in Aceh province will increase.Keywords : Conflict, success, construction projects, Aceh ProvinceAbstrak: Dalam pelaksanaan proyek sering muncul kendala, apabila tujuan proyek tidak tercapai sebagaimana mestinya. Permasalahan ini apabila tidak dikelola dengan baik maka akan menjadi konflik (dispute) atau perselisihan antara unsur-unsur yang terlibat dalam pelaksanaan proyek. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor serta faktor dominan yang menyebabkan terjadi konflik pada proyek konstruksi di Provinsi Aceh, serta menganalisis bentuk hubungan dan pengaruh faktor-faktor konflik terhadap keberhasilan proyek konstruksi di Provinsi Aceh. Proyek yang diamati adalah proyek konstruksi yang telah selesai dilaksanakan mulai dari tahun 2008-2015, dengan sumber dana yang berasal dari APBA dan APBK. Faktor-faktor penyebab terjadinya konflik dalam pelaksanaan proyek konstruksi di Provinsi Aceh adalah disebabkan oleh faktor owner, faktor konsultan, faktor kontraktor, faktor kondisi proyek, faktor sumber daya manusia, dan faktor kontrak dan spesifikasi. Faktor dominan penyebab terjadinya konflik dalam pelaksanaan proyek konstruksi di Provinsi Aceh adalah disebabkan faktor owner, dengan nilai mean sebesar 4,253. Hubungan faktor-faktor konflik terhadap keberhasilan proyek konstruksi di Provinsi Aceh, adalah mempunyai hubungan yang sangat tinggi dengan nilai koefisien korelasi sebesar 0,921. Pengaruh faktor-faktor konflik terhadap keberhasilan proyek konstruksi di Provinsi Aceh, yang paling berpengaruh adalah faktor kondisi proyek, dengan nilai koefisien regresi sebesar 1,021. Hal ini menunjukkan bahwa apabila faktor kondisi proyek ditangani dengan baik, sedangkan faktor-faktor lainnya tetap, maka keberhasilan proyek konstruksi di Provinsi Aceh akan semakin meningkat.Kata kunci : Konflik, keberhasilan, proyek konstruksi, Provinsi Aceh